Effect of Enset(Enset Venitercusem) Based Land Use on Soil Properties in Southern Ethiopia : A Review - Damte Balcha Gadana (International Journal of Scientific Research in Civil Engineering, 2021)
Land use influences soil characteristics and governs sustainable use of soil resources in an Ethiopia. The acidic soils in highland areas of Ethiopia limit crop productivity due to unfavorable soil conditions for the plant growth. A choice of land use that alleviates the soil acidity and improves soil properties may go a long way in maintaining soil quality and its productivity potential. Therefore, this review was focused principally on the potential land use minimizing the ill effect of soil acidity and improving the soil from the prevalent enset, grassland and cereal based land uses in Southern, Ethiopia. Soil nutrient and organic matter depletion, acidification and soil erosion losses as result of inappropriate land use practices have become major cause of concern for agricultural soils in the Ethiopian highlands. Different research result indicated in Ethiopia the enset based land use type significantly decreased soil acidity (pH and exchangeable acidity) and improved other physical (bulk density, total porosity, soil moisture content) and chemical (contents of organic matter, total N, available P and exchangeable basic cations, Cation exchange capacity, percent base saturation and contents of acidic cations) characteristics compared to grassland and cereal based cultivated land. The grassland use also effected significant improvement in soil characteristics, except content of available P, compared to cereal based land use.